Some Properties of Furuta Type Inequalities and Applications - Jiangtao Yuan; Caihong Wang (Abstract and Applied Analysis)
This work is to consider Furuta type inequalities and their applications. Firstly, some Furuta type inequalities under A≥B≥0 are obtained via Loewner-Heinz inequality; as an application, a proof of Furuta inequality is given without using the invertibility of operators. Secondly, we show a unified satellite theorem of grand Furuta inequality which is an extension of the results by Fujii et al. At the end, a kind of Riccati type operator equation is discussed via Furuta type inequalities.